THE ROAD TO VIOLENCE – THE OPPRESSION THEORY AND THE ISLAMIC STATE PROPAGANDA - Alina-Bianca COSCA (Romanian Intelligence Studies Review)
Violent islamist radicalization continues to be a factor of insecurity and social instability. Starting from the theoretical framework offered by the theory of oppression and F. M. Moghaddam’s radicalization model, the purpose of this paper is to highlight the role the main elements of this theory can have in the propaganda of the terrorist organization Islamic State and in the relationship between it and the radicalization processes. More specifically, within the research carried out, we undertook a content analysis based on the thematic coding employing codes and sub-codes resulting from the theoretical framework. These codes were applied on the publications of the Islamic State, Rumiyah, (issues 3-4/2016, 5-7/2017) and Voice of Khurasan (VoK) (issues 16/2022, 21/2022, 23/2023, 29/2023, 30/2023). The main findings of the research highlighted the fact that: 1) perceived oppression has an effect on violent disinhibition, 2) there is a similarity between the constituent elements of the theory of oppression and the constituent elements on the basis of which propaganda and the IS message are created. This similarity is highlighted in the use of specific terms (found in the sub-codes used for content analysis), promoted in Rumiyah and VoK to describe those considered enemies, but also in the way the attackers committed terrorist actions, using the most brutal forms of violence against perceived oppressors.